THE EFFECT OF WEB QUALITY AND PERCEIVED OF USEFULNESS ON BEHAVIOR INTENTION TO USE AMONG SHOPEEFOOD USERS IN SAMARINDA - Pawesty, Enik; Anggreini, Fevica Dwi; Ariandi, Muhammad Amir; Said, Muhammad; Fauziah, Fenty (Jurnal Ekonomi dan Manajemen, 2022)
This study focuses on the effect of the relationship between variables consisting of Web Quality on Perceived Usefulness, Web Quality on Behavior Intention, and Perceived Usefulness on Behavior Intention. The object of this research is Shopeefood users in Samarinda City. This study uses a quantitative approach method. Using primary data and research data collected using a survey method with questionnaires. The research sample is 90 data and using Structural Equation Modeling (SEM) analysis tools with Smart-PLS Software. The results of this study are Web Quality has a significant positive effect on Perceived Usefulness, Web Quality has a significant positive effect on Behavior Intention, and Perceived Usefulness has a significant positive effect on Behavior Intention. The value of the greatest relationship path is found in the relationship between the Web Quality variable and Perceived Usefulness. There is a direct and indirect relationship in this study, the results of the study show that the direct effect is greater than the indirect effect. The researcher's suggestion to Shopeefood, Shopeefood should further improve the Web Quality to increase Behavior Intention for interest to use Shopeefood in a sustainable manner.